Cover Image, Volume 85, Issue 7. Issue 7 (July 2017) - Rath, Emma M.; Duff, Anthony P.; Gilbert, Elliot P.; Doherty, Greg; Knott, Robert B.; Church, W. Bret
Abstract : The cover image, by Emma M. Rath et al., is based on the Article Neutron scattering shows a droplet of oleic acid at the center of the BAMLET complex, DOI:10.1002/prot.25298 .